2015
DOI: 10.1002/dac.2933
|View full text |Cite
|
Sign up to set email alerts
|

A secure and effective biometric‐based user authentication scheme for wireless sensor networks using smart card and fuzzy extractor

Abstract: SUMMARYUser authentication is a prominent security requirement in wireless sensor networks (WSNs) for accessing the real-time data from the sensors directly by a legitimate user (external party). Several user authentication schemes are proposed in the literature. However, most of them are either vulnerable to different known attacks or they are inefficient. Recently, Althobaiti et al. presented a biometric-based user authentication scheme for WSNs. Although their scheme is efficient in computation, in this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
107
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(108 citation statements)
references
References 47 publications
(94 reference statements)
0
107
0
Order By: Relevance
“…In 2016, Alizadeh et al [20] presented a comprehensive survey of authentication schemes of mobile cloud computing (MCC) to explain MCC authentication and differentiate it with that of cloud computing schemes. However, in this paper we performed the cryptanalysis of A.K.Das [17] scheme and found that it is susceptible to stolen smart card attack. Similarly, we found that Choi et al [21] (proposed in 2016), Park et al [22] (introduced in 2016), and Moon et al's [23] (proposed in 2017) schemes are also insecure against various security attacks as we have illustrated in Section 4 of this paper.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2016, Alizadeh et al [20] presented a comprehensive survey of authentication schemes of mobile cloud computing (MCC) to explain MCC authentication and differentiate it with that of cloud computing schemes. However, in this paper we performed the cryptanalysis of A.K.Das [17] scheme and found that it is susceptible to stolen smart card attack. Similarly, we found that Choi et al [21] (proposed in 2016), Park et al [22] (introduced in 2016), and Moon et al's [23] (proposed in 2017) schemes are also insecure against various security attacks as we have illustrated in Section 4 of this paper.…”
Section: Related Workmentioning
confidence: 99%
“…In 2015, A.K. Das [17] proposed fuzzy extractor based authentication scheme which resists well known security attacks of WSNs and have more security features compared to Althobaiti et al (2013) [18] scheme. Sharaf et al [19] proposed (in 2016) an object authentication system in order to exploit device-specific data, known as fingerprints, to authenticate the objects associated with the IoT.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In some schemes, [5] √ × √ Jung et al [6] √ × × Fan et al [7] × × × Amin and Biswas [8] × × × Nam et al [9] × × √ Lu et al [10] √ √ × Zhao et al [11] √ × × Hou et al [12] × × × Farash et al [13] × × × Turkanović et al [14] × × × PriAuth √ √ √ all the users share the same key to encrypt their identities, this means the encrypted identity could be decrypted by a malicious or curious user using the same key [5,6,10,13]. Some of the schemes fail to enable the anonymity of the user or sensor, such as [37][38][39]. We adopt the ECC based method to enable the anonymity, which is similar to [15][16][17][18][19][20][21] because "ECC requires smaller keys compared to non-ECC cryptography (based on plain Galois fields) to provide equivalent security" [40].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, biometricbased user authentication is inherently more secure and reliable than conventional authentication schemes. [20][21][22] In 2010, Yuan et al 18 proposed the first biometricbased user authentication scheme for WSNs. Their scheme was very efficient because it used only the hash function.…”
Section: Introductionmentioning
confidence: 99%